When is My Baby Going Home? Moderate to Late Preterm Infants are Discharged at 36 Weeks Based on Admission Data - Higgins Joyce, Alanna; Sengupta, Arnab; Garfield, Craig F.; Myers, Patrick (American Journal of Perinatology, 2019)
Objective This study evaluates the effect of admission characteristics of uncomplicated moderate to late preterm infants on timing of discharge. One of the first questions that families of infants admitted to the Neonatal Intensive Care Unit (NICU) ask is, “When is my baby going home?” Moderate to late preterm infants are the largest cohort of NICU patients but little data exist about their length of stay (LOS).Study Design A retrospective electronic chart review was completed on 12,498 infants admitted to our NICU between January 1, 2009 and December 31, 2015. All inborn infants with a gestational age between 320/7 and 366/7 weeks were studied.Results A total of 3,240 infants met our inclusion criteria. The mean postmenstrual age at discharge was 363/7 weeks. Infants who were small for gestational age were significantly more likely to have an increased LOS. Infants born between 34 and 366/7 weeks had a significantly increased LOS if they had respiratory distress syndrome. Admission diagnoses of neonatal abstinence syndrome, meconium aspiration syndrome, hydrops, hypoxic ischemic encephalopathy, biliary emesis, ABO incompatibly, and a genetic diagnosis all had increased LOS for all late preterm infants.Conclusion For uncomplicated moderate to late preterm infants, clinicians can counsel families that their infants will likely be discharged at 36 weeks of postmenstrual age. Small for gestational age infants and those with specific diagnoses may stay longer.
Keywords: prematurity; length of stay; discharge; families; communication